Modal analysis of wave motion in inhomogeneous waveguides which are modelled by FEM - Spacapan, Igor; Premrov, Miroslav (Computer Assisted Methods in Engineering and Science, 2004)
This paper presents a simple computing procedure for the analysis of the wave motion in infinite layered waveguides via the analysis of the propagating wave modes. Waveguides may have irregular inclusions, which yields complicated reflections of waves, and an analytical solution is practically not feasible. The section of the waveguide, where we want to analyze the displacements and stress waves, is modelled by finite elements using standard programs for FEM. The external problem is solved as an internal one, while the radiation conditions are satisfied exactly. The procedure only some simple mathematical manipulations and is performed in the frequency domain. It yields exact results and a clear insight into the propagating wave modes. The results of the first presented numerical example are compared to the exact ones, while in the second example the foundation represents an irregularity in the waveguide composed of two layers.